Primer Design and Optimization of Annealing Temperature for Gene Amplification GSTL2 on Rice - Violita, Violita; Achyar, Afifatul; Zulyusri, Zulyusri; Atifah, Yusni; Putri, Dwi Hilda; Nabilah, Rezi (Al-Kauniyah: Jurnal Biologi, 2024)
AbstractGlutathione S-Transferase is a superfamily enzyme that has many roles for living things, especially in the detoxification of Reactive Oxygen Species (ROS), one of which is rice plants. One gene of this family that has a role for plants is GSTL2 This gene is known to have a contribution to Arabidopsis and Oryza sativa L. against abiotic stress. To find out how this gene expression is requires a primer to specifically amplify this gene, and an optimal annealing temperature to support the success of the primer. This study aims to design primers and determine the optimal annealing temperature for gene amplification GSTL2. Primers were designed using the Primer3, which were then analyzed with Genious Prime based on good primer criteria and optimizing the annealing temperature which was carried out using gradient PCR. The results of this study obtained a primer pair is forward 5’-TTCGAAGGGCCAGCATTACT-3’ primer reverse 5’-CAATGTCCACCAAGCTGAA-3’. The primer pair has a length of 20 nt, with melting temperature (Tm) 59–59,4 °C, and GC content 50%. The primer forward there is a secondary structure in the form of a self-dimer with (Tm) 6.2 °C. The primer pair can amplify gene sequences GSTL2 by producing a PCR product 224 bp. The annealing temperature of 60 °C resulting in a single thick, bright DNA strand.AbstrakGlutathione S-Transferase merupakan enzim superfamily yang memiliki banyak peranan bagi makhluk hidup terutama dalam detoksifikasi Reactive Oxygen Species (ROS), salah satunya tumbuhan. Salah satu gen dari famili ini yang memiliki peranan bagi tanaman adalah GSTL2. Gen ini diketahui memiliki kontribusi bagi tanaman Arabidopsis dan Oryza sativa L. terhadap stres abiotik. Untuk mengetahui bagaimana ekspresi gen GSTL2 ini dibutuhkan primer untuk mengamplifikasi gen ini secara spesifik, di samping itu suhu annealing yang optimal untuk menunjang keberhasilan primer. Penelitian ini bertujuan untuk mendesain primer dan menentukan suhu annealing yang optimal untuk mengamplifikasi gen GSTL2. Primer didesain menggunakan tools Pick Primer dan Geneious Prime, yang kemudian dianalisis secara in silico berdasarkan kriteria primer yang baik. Serta optimasi suhu annealing yang dilakukan menggunakan gradient PCR. Hasil penelitian ini diperoleh sepasang primer dengan panjang masing-masing primer 20 nt, primer forward 5’-TTCGAAGGGCCAGCATTACT-3’ primer reverse 5’-CAATGTCCACCAAGCTGAA-3’. Pasangan primer dapat mengamplifikasi sekuen gen GSTL2 dengan menghasilkan produk PCR sebesar 224 bp pada suhu annealing 60 °C.